Acupuncture for stroke survivors with cardiovascular comorbidities: protocol of a pooled analysis of randomized controlled trials - Zhang, Lanfang; Mei, Zubing; Xu, Zhenhua (Frontiers in Neurology, 2025)
BackgroundStroke remains a leading cause of long-term disability globally, often complicated by cardiovascular comorbidities such as hypertension, atrial fibrillation, and coronary artery disease. These comorbidities not only increase the risk of recurrent strokes but also complicate recovery, making effective rehabilitation strategies crucial. Acupuncture, a traditional Chinese medicine practice, has gained attention as a potential complementary therapy for stroke rehabilitation. This protocol outlines a pooled analysis of randomized controlled trials (RCTs) aimed at evaluating the effectiveness and safety of acupuncture in improving neurological function, quality of life, and reducing stroke recurrence in stroke survivors with cardiovascular comorbidities.Methods and analysisThis pooled analysis will adhere to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. We will include RCTs that assess acupuncture interventions compared to placebo acupuncture, standard care, or no intervention in adult stroke survivors with at least one cardiovascular comorbidity. Comprehensive literature searches will be conducted in databases including PubMed, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), and CINAHL, covering all studies published from inception to the most recent update. Two independent reviewers will screen titles and abstracts, and full-text articles will be reviewed to confirm eligibility. Data extraction will focus on participant characteristics, intervention specifics, outcomes related to neurological function, quality of life, stroke recurrence, and adverse events. The risk of bias will be assessed using the Cochrane Risk of Bias tool. A random-effects meta-analysis will be conducted to account for heterogeneity across studies, and subgroup analyses will explore the impact of different stroke types, cardiovascular comorbidities, and acupuncture techniques on outcomes.Discussion and conclusionThis study aims to provide a comprehensive evaluation of the role of acupuncture as an adjunctive treatment for stroke rehabilitation in patients with cardiovascular comorbidities. The findings are expected to contribute to the evidence base regarding the efficacy and safety of acupuncture in this specific patient population, potentially influencing clinical practice guidelines and promoting the integration of acupuncture into standard stroke care protocols. Despite the potential benefits, challenges such as variability in acupuncture techniques and patient characteristics across studies may affect the generalizability of the results. Nevertheless, this study will offer valuable insights into optimizing rehabilitation strategies for stroke survivors with complex clinical profiles.PROSPERO registration noCRD42024576156.